Đánh giá ảnh hưởng của động đất tới các công trình xây dựng tại khu vực đô thị Thành phố Hồ Chí Minh - Phương, Nguyễn Hồng; Dũng, Hoàng Đôn (Vietnam Journal of Earth Sciences, 2012)
summaryAssessment of building damage due to earthquakes in urban area of Ho Chi Minh cityThis paper presents some preliminary results of building damage assessment due to earthquakes in Ho Chi Minh City. A methodology for urban seismic risk assessment was applied to six most typical building classes available in the 1 and 3 districts, downtown of the Ho Chi Minh City. GIS technology was used to develop a plausible earthquake scenario and a computational tool to evaluate the building damage level by defining four damage states : Slight, Moderate, Extensive and  Complete. The results show extremely low probability of the Complete state of damage, which is not exceeding 0.023 %. The highest damage rate is for the residential areas, especially for the low-rise unreinforced masonry bearing walls building (URML type), with damage probability of 13.05 %, 7.18 % and 1.61 % for the Slight, Medium and Extensive states, respectively.The building damage estimation quantifies the insight and imagination of the risk level an urban community has to face when large earthquakesoccur in areas, within or adjacent to the city. This forecasting capability will enable authorities to anticipate the consequences of future earthquakes and to develop plans and strategies for reducingurban risk in the future.